Mechanical properties of vulcanized natural rubber nanocomposites containing functional ceramic nanoparticles - Bellucci, F. S. [UNESP]; Budemberg, E. R.; Nobre, Marcos Augusto Lima [UNESP]; De Saja, J. A.; Aroca, R. F.; Rodríguez-Pérez, M. A.; Job, A. E. [UNESP] (American Scientific Publishers, 2013)
Rubber nanocomposites containing different concentrations of ferroelectric and paramagnetic nanoparticles were fabricated. Nanostructures of ferroelectric potassium strontium niobate and paramagnetic nickel-zinc ferrite were synthesized using a modified polyol method. The nanoparticle characterization was carried out by transmission electron microscopy and X-ray diffraction, showing that the materials were produced with nanometer dimensions, specific crystallinity and microstrain. Mechanical tests such as hardness type Shore A, stress-strain and compression resistance were performed. They showed that increasing the concentration of nanoparticles enhance the rigidity of vulcanized films of natural rubber and this change is more pronounce for the nanocomposites formed with ferrite nanoparticles, likely due to the effect of its morphological and surface properties. © 2013 by American Scientific Publishers.
Keywords: Mechanical properties; Nanoparticles; Rubber nanocomposites; Structural properties